Kinematic Modeling of Mechanocatalytic Depolymerization of α‐Cellulose and Beechwood. Issue 3 (11th January 2018) - Kessler, Martin; Woodward, Robert T.; Wong, Narumi; Rinaldi, Roberto
Abstract: Mechanocatalytic depolymerization of lignocellulose presents a promising method for the solid‐state transformation of acidified raw biomass into water‐soluble products (WSPs). However, the mechanisms underlining the utilization of mechanical forces in the depolymerization are poorly understood. A kinematic model of the milling process is applied to assess the energy dose transferred to cellulose during its mechanocatalytic depolymerization under varied conditions (rotational speed, milling time, ball size, and substrate loading). The data set is compared to the apparent energy dose calculated from the kinematic model and reveals key features of the mechanocatalytic process. At low energy doses, a rapid rise in the WSP yield associated with the apparent energy dose is observed. However, at a higher energy dose obtained by extended milling duration or high milling speeds, the formation of a substrate cake layer on the mill vials appear to buffer the mechanical forces, preventing full cellulose conversion into WSPs. By contrast, for beechwood, there exists a good linear dependence between the WSP yield and the energy dose provided to the substrate over the entire range of WSP yields. As the formation of a substrate cake in depolymerization of beechwood is less severe than that for the cellulose experiments, the current results verify the hypothesis regarding the negative effect of a substrate layer formed on the mill vials upon the depolymerization process. Overall, the current findings provide valuable insight into relationships between the energy dose and the extent of cellulose depolymerization effected by the mechanocatalytic process. Abstract : Because impact matters : The mechanisms underlining the utilization of mechanical forces in cellulose depolymerization arepoorly understood. A kinematic model, applied to the milling process to assess the energy dose transferred to cellulose, demonstrates a relationship between the apparent energy dose and the extent of cellulose depolymerization effected by the mechanocatalytic process.